(untitled) (Cambridge, UK,New York, 2004)
In the passionate and divisive debate about globalisation, there is growing consensus concerning the need to reduce the level of subsidies in agriculture and to open up the markets of the developed world more to the farmers of the developing world. However, whilst NGOs such as Oxfam may agree on this point with free trade economists, governments in Europe and the US seem reluctant to give up their protectionist habits. This collection provides the definitive survey of the importance of agricultural reform to the future of the world's trading system
Keywords: Produce trade,Tariff on farm produce,Thương mại quốc tế; Government policy,International cooperation